The effect of MoS2 modulated doping with molybdenum-oxide on the photovoltaic performance for MoS2/n-Si heterojunction solar cells. (15th September 2020) - Zhang, Yu; Su, Ping; Liu, Linqing; Qiu, Pengfei; Su, Li; Fu, Guangsheng; Yu, Wei
Graphical abstract: Achieving large Fermi energy splitting under illumination is critical for improving the performance of the photovoltaic devices. We conducted the energy band structure modulation of MoS2 thin films to realize its photovoltaic operation on n-type c-Si and improve the photovoltaic performance of the formed MoS2 /n-Si heterojunction solar cells. By capping with a MoOx overlayer, there is electrons orientation flowing from the valence band of MoS2 into the O-deficiency states of MoOx due to their energy level overlap, which leads to the Fermi level downshift of the MoS2 films and consequently its conductive type conversion. After the MoS2 layer doped, we found that the built-in electric field of the fabricated MoS2 /n-Si heterojunction devices greatly improved owing to the larger hetero-interface Fermi level differences. And, the defects recombination losses at the hetero-interface also reduced because of the holes selectively extracting effect of the O-vacencies in MoOx . As a result, the photo-generated carriers separation and extraction are both enhanced at the hetero-interface, so that the MoS2 /n-Si devices exhibited excellent photovoltaic performance under the modulation doping effect. The conclusive power conversion efficiency of the doped MoS2 /n-Si solar cells is of 5.47% with respectively optimized electrical parameters (Voc of 289 mV, FF of 60.72 and Jsc of 31.25 mA/cm 2 ). This observation of MoOx modulation doping effect on large-area sputtering MoS2 could help in building a more appropriate interface carrier transport mechanism in photovoltaic and optoelectronic device applications of 2D materials. Highlights: The PV application of semiconducting MoS2 on n-type c-Si is realized. The energy band structure of MoS2 is modulated by MoOx doping scheme. Doping mechanism lies on carriers contact transfer due to energy band overlap. Interface carriers transport efficiently enhanced by larger Fermi level splitting. The PV performance of MoS2 /n-Si devices improved significantly with MoOx doping. Abstract: Achieving large Fermi energy splitting under illumination is critical for improving the performance of photovoltaic devices. In this work, we conducted the energy band structure modulation of MoS2 thin films via MoOx doping scheme to realize its photovoltaic operation on n-type c-Si by magnetron sputtering. It is found that, by capping a MoOx overlayer, the MoS2 electrons density decreased and the Fermi level shifted ~0.4 eV towards valence band, consequently the MoS2 conductive type changing. With this doped MoS2 layer, the built-in electric field of fabricated MoS2 /n-Si heterojunction devices greatly improved and exceeded 400 mV owing to the larger interface energy-level differences. Meanwhile, the defects recombination losses reduced benefiting from the holes-selective behavior of O-deficiencies in MoOx, so that the photo-generated carriers extraction process were promoted. As a result, the doped MoS2 /n-Si devices showed excellent rectification behavior with rectifying ratio to 10 5 and ideality of 1.12. The TRPL spectrums corroborated the enhanced carrier transport mechanism at MoS2 /n-Si interface by MoOx modulation doping effect. Correspondingly, the significant improvement of doped MoS2 /n-Si solar cells performance (Voc of 289 mV, FF of 60.72% and Jsc of 31.25 mA/cm 2 ) was achieved, exhibiting an optimized conversion efficiency of 5.47%. The UPS analysis revealed that the doping mechanism of MoOx /MoS2 stacks lies in energy band overlap and electrons contact transfer between these two materials. This observation of MoOx modulation doping effect on large-area sputtering MoS2 could help in building a better interface carrier transport in photovoltaic and optoelectronic applications of 2D materials.